Безмасова границя рівнянь Баргмана–Вігнера для масивного гравітона - Hradyskyi, A. V.; Stepanoskiy, Yu. P. (Publishing house "Academperiodika", 2018)
Information about the discovery of gravity waves attract attention to the graviton’s mass problem. The massive graviton is a spin-2 particle with a non-zero mass. In this work, relativistic wave equations for a massive graviton have been studied in the limiting case of zero particle mass. The equations for the non-zero-mass graviton are based on the Bargman–Wigner equations in the five-dimensional space-time with the (++++−) signature. In the massless limit of massive graviton, all states with possible helicity values –0 (LL-graviton), ±1 (TL-graviton), and ±2 (TT-graviton) –are preserved.